Pastoral Bagi Keluarga Dalam Situasi Khusus Menurut Paus Fransiskus Dalam Anjuran Apostolik Amoris Laetitia - Gerardus Rahmat Subekti (Media (Jurnal Filsafat dan Teologi), 2021)
The article deals with pastoral care for family according to Amoris Laetitia. The author’s concern is to discuss the pastoral steps for the families in the face of crisis situations: What kind of pastoral steps can be organized to assist families in crisis situations? This article is based on the study of ecclesial document Amoris Laetitia, a post-synodal apostolic exhortation by Pope Francis addressing the pastoral care of families. First of all, the article describes the basic thoughts of this document, especially those related to the reality and ideals of family life. Then, it shows some practical pastoral thoughts for assisting families in special situations. The results can be a significant contribution for the Church in terms of its important duties and responsibilities in assisting the families today, but also for family pastoral activists. This description concludes that the crisis situation faced by families is not a fact to be constantly regretted, but an opportunity for the Church to show God's mercy to those who are struggling in difficult situations.